Identity‐based proxy signatures: a generic construction and a concrete scheme from RSA. Issue 18 (25th May 2015) - Asaar, Maryam Rajabzadeh; Salmasizadeh, Mahmoud; Boyd, Colin
Abstract: Proxy signatures allow an entity to delegate its signing capability to a proxy which can sign messages on behalf of the delegator. We examine identity‐based versions of proxy signatures which employ identity strings in place of randomly generated public keys. First, we give a new generic construction of identity‐based proxy signatures from identity‐based standard signatures and show that our generic construction is secure if the underlying identity‐based standard signature is secure. In addition, we present the first identity‐based proxy signature from Rivest, Shamir and Adleman (RSA), secure under the one‐wayness of RSA in the random oracle model. We should highlight that the proxy key exposure attack cannot be applied to our proposed constructions. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, a secure generic construction for identity‐based proxy signatures from secure identity‐based standard signatures is proposed. Then, the first identity‐based proxy signature from RSA, secure under the one‐wayness of RSA in the random oracle model has been proposed. It should be highlighted that the proxy key exposure attack cannot be applied to these constructions.